DILATED CARDIOMYOPATHY IN A CHILD WITH GRAVES’ DISEASE - Idris, Siti Salamah binti Mohd; Hussain, Suhaimi bin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Individuals diagnosed with Grave’s disease typically exhibit symptoms of hyperthyroidism, including chest pain, palpitations, and weight loss. Uncommonly, patients may also develop cardiomyopathy, a complication that is extremely serious and potentially life-threatening. Its occurrence is higher among middle-aged and elderly patients with pre-existing heart conditions. Although rare in children, we must acknowledge this complication because of its high mortality and morbidity rates. CASE The report details a case of an 11-year-old female with Graves’ disease, thyroid storm, and cardiomyopathy. She had palpitations for almost 2 years, followed by recurrent syncopal attacks for 6 months. Her ‘unexplained’ syncopal attacks were only provided reassurance when she sought medical attention. Upon her first endocrine review, she was in a hyperthyroid state with bilateral exophthalmos, diffuse goitre with signs of heart failure. The initial thyroid function test showed significantly high FT4 levels of 85.6 pmol/L and suppressed TSH. Her TSH Receptor antibody showed elevated levels, and the initial CXR revealed cardiomegaly. She was started with oral carbimazole 30 mg daily, oral propranolol 20 mg 4 times a day, Lugol’s iodine 4 drops 4 times a day, and intravenous hydrocortisone 50 mg q 6 hourly. Two anti-failure medications were used to treat her heart failure. Her symptoms improved, and she was discharged with oral carbimazole and oral propranolol. CONCLUSION It is important to plan an early definitive therapy in this case to prevent future cardiac decompensation during relapse. Medical practitioners need to be aware of the rare presentations of Graves’ disease to avoid delayed diagnosis and treatment.